PENGARUH PRODUK DAN PROMOSI TABUNGAN TAMARAH TERHADAP KEPUTUSAN NASABAH MENABUNG PADA KSPPS BAITUL MAAL WAT-TAMWIL (BMT) EL-USWAH DHARMASRAYA - Nazaruddin Aziz; Biisnillah Biisnillah (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2021)
This study aims to examine the effect of Tamara savings productsmand promotions on customer decisions to save at KSPPS BAITUL MAAL WAT-TAMWIL (BMT) EL-USWAH DHARMASRAYA.The variables used in this study are the dependent variable namely customer decisions (Y) and the independent variable consisting of the product (X1), promotions(X2). The type of data used in this study is quantitative  data. The accumulated data used in this study are  primary data from quenstionnaires and use purposive sampling techinique, data analysis techniques use classical assumption test, multiple linear regression analysis, F test, t test, R test using the SPSS 16 program, The population in this study are customers at KSPPS BAITUL MAAL WAT-TAMWIL (BMT) EL-USWAH DHARMASRAYA, the sample in this study amounted to 96 respondents, the results showed that the product had a significant positive effect on customer decisions to save, the promotion of Tamara savings had a significant positive effect on kep the customer delegate saves, products and promotion of Tamara savings collectively have a significant positive effect on customer decisions to save.